Antecedents And Outcomes Of Job Stress: A Study Among Managers In The Electronics Industry In Penang - Sathasivam, Kumaresan V. (2002)
This research presents an integration of past research and theory that models the relationship of the antecedents of stress and stress outcomes among managers. The scope of this study is limited to electronics firms in the Island of Penang. Stress antecedents relates to organizational sources of stress and the individual's personality traits while stress outcomes relates to psychological distress and job satisfaction.